Manajemen dental dalam memdokumentasikan kekerasan terhadap anak Dental management in documenting child’s abuse - Mega M. Puteri (DiscoverSys Inc., 2012)
Child abuse has increased dramatically over these present years. Child abuse occurs because of several reasons,such as poverty, low education background, and loss parents because of natural disasters. An estimate incidence ofchild abuse according to Komisi Nasional (Komnas) Anak in 2009 there are 1,998 cases, which is considerablyhigh. It showed that society become more consciousness about child abuse. However, there is still small evidence ofchild abuse, due to lack of awareness, knowledge and skills on documenting child abuse. Moreover, most of theinjuries of child abuse occurs at orofacial, so it is needed the awareness of dentist to understand the procedure indocumenting child abuse. The purpose of this study is to improve knowledge and skill of the dentist in documentingchild abuse.